DDRE-40. BIOINFORMATICS ANALYSIS OF GRADE I AND III MENINGIOMA GENE EXPRESSION SUGGESTS MMP28 AS A POSSIBLE POSITIVE PROGNOSTIC INDICATOR. (12th November 2021) - Michelhaugh, Sharon; Dyson, Gregory; Ali-Fehmi, Rouba; Bollig-Fischer, Aliccia; Mittal, Sandeep; Degen, Katherine
Abstract: Meningiomas are the most common primary brain tumor. Grade I meningiomas are slow growing with a good prognosis following surgical resection. High grade meningiomas (II and III) are more aggressive with greater rates of recurrence and poor prognosis despite surgical resection and radiotherapy. This study sought to identify key pathways and genes that contribute to the molecular mechanisms that separate these distinct meningioma phenotypes. FFPE specimens were evaluated and graded by a pathologist. Total RNA was extracted from tissue curls and RNA samples were measured with the Illumina DASL whole genome gene expression assay (n = 29, 374 probes). A log2 transformation was applied to all of the data and quantile normalization using 21 samples. A t-test of the log2 expression of the 10 grade III samples and 11 grade I samples resulted in 1505 differentially expressed genes. The GeneCard Suite's GeneAnalytics tool was used to perform pathway enrichment analysis. Similar to other comparable data sets, DNA Damage, Cell Cycle, EGF/EGFR Signaling, TGF-Beta Signaling, and PI3K-AKT Signaling pathways were among the 20 enriched pathways. Notably, matrix metalloprotease 28 (MMP28, also known as epilysin) was down regulated in grade III meningiomas compared to grade I (III/I expression ratio 0.315; P=0.015). MMP28 is expressed in numerous tissues including the nervous system during development and regeneration. In cancer, MMP28 is thought to enhance epithelial to mesenchymal transition by altering the TGF-B signaling pathways. MMP28 is an indicator of poor prognosis for pancreatic, lung, gastric and hepatic cancers as well as glioblastoma. However, MMP28 has also been reported as down regulated during malignant transformation in colon cancer. Our data suggest that MMP28 may have an alternative role in meningioma and serve as a positive prognostic indicator.